State of free trade in the Americas : 1998 hemispheric business report (Caribbean Latin American Action WashingtonUS, 1998)
Highlights private sector input to the Free Trade Area of the Americas; looks at current trade trends in the hemisphere; and, focuses on business sector perspectives.
DC